De Geodetische Lijn - Teunissen, Peter (1991)
On occasion of his maiden lecture accepting the post as professor in Mathematical Geodesy and Point determination at the Delft University of Technology the author reviews the development of geodetic science since the introduction of Newton's gravity theory, covering the integration of geometry and gravimetrics, location and potentials, planimetry and elevation and static and dynamic theories. Finally the consequences of these developments in adjustment, testing and planning of ground control networks are discussed.